2024
DOI: 10.1038/s41419-024-06578-w
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics treatment promotes vasculogenesis in the brain of glioma-bearing mice

Maria Rosito,
Javeria Maqbool,
Alice Reccagni
et al.

Abstract: In recent years, several studies described the close relationship between the composition of gut microbiota and brain functions, highlighting the importance of gut-derived metabolites in mediating neuronal and glial cells cross-talk in physiological and pathological condition. Gut dysbiosis may affects cerebral tumors growth and progression, but the specific metabolites involved in this modulation have not been identified yet. Using a syngeneic mouse model of glioma, we have investigated the role of dysbiosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…These two groups differed significantly in steroid and tryptophan metabolic pathways, as well as in macrophage and cytotoxic T lymphocyte infiltration [ 10 ]. Previous research has indicated that broad-spectrum antibiotic cocktail (ABX) therapy can lead to tumor-promoting effects by reducing cytotoxic NK cell subsets and impairing microglial function in the intracranial tumor microenvironment [ 100 , 134 ]. These findings are consistent with the results of the aforementioned studies, highlighting the crucial role of the intestinal flora as a target for sensitizing chemotherapeutic agents.…”
Section: Gut Bacteria and Cns Tumorsmentioning
confidence: 99%
“…These two groups differed significantly in steroid and tryptophan metabolic pathways, as well as in macrophage and cytotoxic T lymphocyte infiltration [ 10 ]. Previous research has indicated that broad-spectrum antibiotic cocktail (ABX) therapy can lead to tumor-promoting effects by reducing cytotoxic NK cell subsets and impairing microglial function in the intracranial tumor microenvironment [ 100 , 134 ]. These findings are consistent with the results of the aforementioned studies, highlighting the crucial role of the intestinal flora as a target for sensitizing chemotherapeutic agents.…”
Section: Gut Bacteria and Cns Tumorsmentioning
confidence: 99%
“…The efficacy and toxicity of chemotherapy drugs such as temozolomide may be influenced by gut microbiota metabolism ( 76 ). However, predicting and regulating these interactions to optimize drug efficacy and reduce side effects remains challenging, especially in GBM where patients typically require multiple drug combinations, increasing the complexity of drug microbiota interactions ( 77 ).…”
Section: Dilemma Of the Gut Microbiota In The Treatment Of Gbmmentioning
confidence: 99%